1999
DOI: 10.4269/ajtmh.1999.60.357
|View full text |Cite
|
Sign up to set email alerts
|

Longevity of naturally acquired antibody responses to the N- and C-terminal regions of Plasmodium vivax merozoite surface protein 1.

Abstract: Abstract. In an earlier study, we found that individuals with patent infection had significantly higher IgG antibody titers to the 19-kD C-terminal region of Plasmodium vivax merozoite surface protein 1 (PvMSP1) than individuals treated for malaria 1-4 months earlier. These results suggested that the antibody levels decreased rapidly following treatment. The present study was designed to determine the persistence of antibody response to the N-and C-terminal regions of PvMSP1 after infection with P. vivax in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
107
2
13

Year Published

1999
1999
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(135 citation statements)
references
References 29 publications
13
107
2
13
Order By: Relevance
“…18 The only other report concerning cellular responses to MSP-1 among Brazilians was to P.vivax. 28 The investigators used polypeptides representing the N-and C-terminal regions of the protein and showed PBMC stimulation ranging from 17% to 47% in the malaria-exposed group.…”
Section: Resultsmentioning
confidence: 99%
“…18 The only other report concerning cellular responses to MSP-1 among Brazilians was to P.vivax. 28 The investigators used polypeptides representing the N-and C-terminal regions of the protein and showed PBMC stimulation ranging from 17% to 47% in the malaria-exposed group.…”
Section: Resultsmentioning
confidence: 99%
“…High titers of MSP1 19 -specific antibody are required to achieve such protection [8,9]. In humans, natural infection generates MSP1 19 -specific antibodies, but these appear to be short-lived at least in children, and levels are generally not as high as to other parts of the MSP1 complex [10][11][12][13][14][15]. CD4 + T cell responses are essential for protective immunity in rodent models of malaria and in protective immunity induced by immunization with MSP1 19 [16].…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting with the extensive investigation of the role of Pf MSP-1 19 in naturally acquired immunity, little is known about the immune recognition of the ortholog protein of P. vivax (Pv). In Brazil, high proportions of subjects with detectable antibodies and T-cell responses to PvMSP-1 19 were found in areas of focal transmission (Soares et al 1997(Soares et al , 1999b and high proportions of seropositive subjects were uniformly observed in areas with more stable transmission (Morais et al 2005).…”
mentioning
confidence: 99%